Prenatal dexamethasone exposure-induced a gender-difference and sustainable multi-organ damage in offspring rats via serum metabolic profile analysis. (November 2019) - Chen, Guanghui; Xiao, Hao; Zhang, Jinzhi; Zhang, Huizhen; Li, Bin; Jiang, Tao; Wen, Yajie; Jiang, Yimin; Fu, Kaili; Xu, Dan; Guo, Yu; Ao, Ying; et al.
Graphical abstract: Highlights: PDE-induced on offspring's serum metabolic profiles before and after birth. the indexes of serum liver and kidney function are abnormal in PDE adult rats. PDE-induced the disorders of glucose, protein, lipid metabolism in utero . Changes in bile acids and phosphatidylcholine in utero are continued after birth. Abstract: Prenatal dexamethasone exposure (PDE) induces developmental toxicities of multiple organs in offspring, but its serum metabolic profile changes before and after birth are unclear. Here, we employed a LC–MS-based metabolomic approach to detect serum metabolites of PDE offspring rats in utero and adulthood, and explore its change characteristics and toxicological significances. Meanwhile, the bodyweight, serum index related to hepatic and renal function were detected. As compared to healthy control rats, PDE reduced offspring birthweight but caused postnatal catch-up growth accompanied by adult liver and kidney function injury. In utero, the differential metabolites in response to PDE were mainly manifested as enhanced glycolysis, increased protein breakdown and disordered lipid metabolism, and multiple metabolic pathways were changed, which displayed gender differences. In adulthood, PDE offspring showed fewer and inconsistent types of differential metabolites compared to those in utero, which exhibited significant gender differences. The main differential metabolites induced by PDE included lactic acid, carnitine, cortexolone, bile acid, phosphatidylcholine, uric acid and platelet activating factor, which may participate in dexamethasone multi-organ toxicities and multi-disease susceptibility. In conclusion, PDE could induce a gender-difference and sustainable multi-organ damage in the offspring rats via serum metabolic profile analysis, which will enhance offspring susceptibility to multiple adult diseases.